Effect of levels of self-regulation and situational stress on achievement emotions in undergraduate students: Class, study and testing - de la Fuente, Jesús (2020)
Achievement emotions constitute one important variable among the many variables of students’ learning. The aim of this research was to analyze the differential effect of university students’ levels of self-regulation (1 = low, 2 = medium and 3 = high), and of their level of perceived stress in three academic situations (1 = class, 2 = study time and 3 = testing), on the type of achievement emotionality they experience (positive and negative emotions). The following hypotheses were established: (1) a higher level of student self-regulation would be accompanied by higher levels of positive emotionality and lower levels of negative emotionality and (2) a higher level of situational stress would predispose higher levels of negative emotionality and lower levels of positive emotionality. A total of 520 university students completed three self-reports with validated inventories. Descriptive, correlational, and structural prediction analyses (SEM) were performed, as well as 3 × 3 ANOVAs, under an ex post facto design by selection. The results showed overall fulfillment of the hypotheses, except for a few specific emotions. Implications for prevention and psychoeducational guidance in the sphere of university education are discussed.